Rome sweet home : our journey to Catholicism - Hahn, Scott; Hahn, Kimberly (San Francisco : Ignatius Press, 1993)
Scott and Kimberly Hahn tell the stories of their lives and religious backgrounds, and explain how they came to be converted to the Catholic faith.
1. From the cradle to Christ -- 2. From ministry to marriage --3. New conceptions of the covenant -- 4. Teaching and living the covenant as a family -- 5. Scott's search for the church -- 6. One comes home to Rome -- 7. The struggles of a mixed marriage --8. A Rome-antic reunion -- 9. Catholic family life.
Keywords: Hahn, Scott; Hahn, Kimberly; Catholic converts -- Biography; Catholics -- Biography